2015
DOI: 10.1038/ncomms10088
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral and central amygdala differentially recruit and maintain dorsolateral striatum-dependent cocaine-seeking habits

Abstract: In the development of addiction, drug seeking becomes habitual and controlled by drug-associated cues, and the neural locus of control over behaviour shifts from the ventral to the dorsolateral striatum. The neural mechanisms underlying this functional transition from recreational drug use to drug-seeking habits are unknown. Here we combined functional disconnections and electrophysiological recordings of the amygdalo-striatal networks in rats trained to seek cocaine to demonstrate that functional shifts withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
102
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 73 publications
7
102
0
Order By: Relevance
“…Further, the reduction of associated executive functions, particularly inhibitory control, may result in unwanted habitual behaviours being more difficult to suppress thus further diminishing flexible behavioral control. Amygdala regions may also critically contribute to the expression of goal-directed and habitual behavior, and perhaps the transition from one to the other as shown recently for cocaine (Murray et al, 2015). The basolateral amygdala is important for assigning motivational significance to stimuli based on sensory-specific properties, and damage to this structure impairs sensitivity to outcome devaluation and outcome-specific PIT (Corbit & Balleine, 2005).…”
Section: Mechanismsmentioning
confidence: 84%
“…Further, the reduction of associated executive functions, particularly inhibitory control, may result in unwanted habitual behaviours being more difficult to suppress thus further diminishing flexible behavioral control. Amygdala regions may also critically contribute to the expression of goal-directed and habitual behavior, and perhaps the transition from one to the other as shown recently for cocaine (Murray et al, 2015). The basolateral amygdala is important for assigning motivational significance to stimuli based on sensory-specific properties, and damage to this structure impairs sensitivity to outcome devaluation and outcome-specific PIT (Corbit & Balleine, 2005).…”
Section: Mechanismsmentioning
confidence: 84%
“…It is striking that modulation of IfL-C activity during consumption was comparable across all conditions, suggesting that processing of contingency and value information is dissociable in IfL-C as a function of response strategy. It should be noted that while loss of IfL-C function is sufficient to occlude habitual reward seeking (Coutureau and Killcross, 2003; Killcross and Coutureau, 2003; Smith et al, 2012), it is by no means the only structure necessary for habits (Yin et al, 2004; Lingawi and Balleine, 2012; Murray et al, 2015). Indeed, using a maze-based task, previous studies demonstrated that coordination between IfL-C and dorsolateral striatum activity is crucial for the development of inflexible behaviors (Smith and Graybiel, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of IfL-C glutamatergic neurons in the regulation of response strategy (Smith et al, 2012), it is therefore likely that the IfL-C facilitates habitual reward seeking through its action at downstream targets. IfL-C targets multiple structures necessary for the regulation of response strategy selection, including subregions of the amygdala that are differentially involved in the acquisition and expression of habits (Lingawi and Balleine, 2012; Murray et al, 2015). Downstream targets of the IfL-C also include the nucleus accumbens in which IfL-C inputs are required for contingency-mediated behaviors such as appetitive extinction learning (Peters et al, 2008, 2009) and outcome selective Pavlovian-to-instrumental transfer (Keistler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Following 1 week of habituation to the colony, Lister Hooded rats underwent either both intravenous catheter implantation and bilateral aDLS cannulations (α‐flupenthixol experiment, α‐flu, n = 9) or only the former (N‐acetylcysteine experiment, NAC , n = 14) a week before beginning training. Rats acquired heroin self‐administration under a fixed ratio 1 schedule of reinforcement ( FR 1) under which they were maintained for 10 consecutive daily sessions which were followed by the early stage seeking tests (Murray et al ., , , ). During the early stage seeking tests, rats were challenged to seek heroin over 15 min with CS presented contingently upon each lever press.…”
Section: Methodsmentioning
confidence: 99%